Inner-volume echo volumar imaging (IVEVI) for robust fetal brain imaging - Nunes, Rita G.; Ferrazzi, Giulio; Price, Anthony N.; Hutter, Jana; Gaspar, Andreia S.; Rutherford, Mary A.; Hajnal, Joseph V. (Magnetic Resonance in Medicine, 2018)
Purpose: Fetal functional MRI studies using conventional 2-dimensional single-shot echo-planar imaging sequences may require discarding a large data fraction as a result of fetal and maternal motion. Increasing the temporal resolution using echo volumar imaging (EVI) could provide an effective alternative strategy. Echo volumar imaging was combined with inner volume (IV) imaging (IVEVI) to locally excite the fetal brain and acquire full 3-dimensional images, fast enough to freeze most fetal head motion. Methods: IVEVI was implemented by modifying a standard multi-echo echo-planar imaging sequence. A spin echo with orthogonal excitation and refocusing ensured localized excitation. To introduce T2* weighting and to save time, the k-space center was shifted relative to the spin echo. Both single and multi-shot variants were tested. Acoustic noise was controlled by adjusting the amplitude and switching frequency of the readout gradient. Image-based shimming was used to minimize B0 inhomogeneities within the fetal brain. Results: The sequence was first validated in an adult. Eight fetuses were scanned using single-shot IVEVI at a 3.5 × 3.5 × 5.0 mm3 resolution with a readout duration of 383 ms. Multishot IVEVI showed reduced geometric distortions along the second phase-encode direction. Conclusions: Fetal EVI remains challenging. Although effective echo times comparable to the T2* values of fetal cortical gray matter at 3 T could be achieved, controlling acoustic noise required longer readouts, leading to substantial distortions in single-shot images. Although multishot variants enabled us to reduce susceptibility-induced geometric distortions, sensitivity to motion was increased. Future studies should therefore focus on improvements to multishot variants. Magn Reson Med 80:279–285, 2018. © 2017 International Society for Magnetic Resonance in Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: echo volumar imaging; fast acquisition; fetal fMRI; inner volume imaging; localized excitation